Hydrochemistry, hydrogen and oxygen isotopes, and radon in waters of the greater Timbavati catchment, South Africa - Dippenaar, Matthys Alois (University of Pretoria, 2024)
Dissertation (MSc (Hydrogeology))--University of Pretoria, 2024.